2021
DOI: 10.1177/0963721421995489
|View full text |Cite
|
Sign up to set email alerts
|

The Scams Among Us: Who Falls Prey and Why

Abstract: Not a week goes by without stories about scams appearing in popular media outlets. Given the ease with which scams can be circulated, they have become one of the most common crimes globally, inflicting high emotional, financial, and psychological tolls on millions of individuals. Despite their profound and pervasive impact, researchers know relatively little about why some individuals fall victim to scams but others remain immune to the techniques utilized by scammers to lure potential victims. For example, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 30 publications
0
9
0
1
Order By: Relevance
“…The main concern that led to this study was the alarming rate of e-commerce scams cases with astronomical financial losses, as reported by several studies around the world (Paintal, 2021;Hanoch & Wood, 2021;Sinha et al, 2020;Zahari et al, 2019). In Malaysia, statistics showed that approximately 5.2 billion (RM) of financial losses were recorded from 2018 -May 2022 due to e-commerce scam-related cases (Shah & Chudasama, 2021).…”
Section: Problem Statementmentioning
confidence: 98%
“…The main concern that led to this study was the alarming rate of e-commerce scams cases with astronomical financial losses, as reported by several studies around the world (Paintal, 2021;Hanoch & Wood, 2021;Sinha et al, 2020;Zahari et al, 2019). In Malaysia, statistics showed that approximately 5.2 billion (RM) of financial losses were recorded from 2018 -May 2022 due to e-commerce scam-related cases (Shah & Chudasama, 2021).…”
Section: Problem Statementmentioning
confidence: 98%
“…Prior research on fraud risk factors has a number of methodological limitations. First, while research indicates that different types of people are uniquely susceptible to different frauds, and many scams target certain groups of people more than others (Button et al, 2009; DeLiema et al, 2020; Hanoch & Wood, 2021; K. Pak & Shadel, 2011), many studies group victims of very different scams together in statistical models (e.g., Schoepfer & Piquero, 2009; Titus et al, 1995). This can obscure victim risk factors that vary by fraud type.…”
Section: Introductionmentioning
confidence: 99%
“…Globally, Internet scams have been acknowledged as one of the most common crimes, inflicting higher emotional, financial and psychological tolls on individuals worldwide (Hanoch and Wood 2021). For example, in the United States, the 2021 Internet Crime Report of the Federal Bureau of Investigation (FBI) indicated that 847,376 complaints were received, a 7% increase from 2020, with financial losses exceeding $6.9 billion (FBI 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In dating scams, a global loss of $547 million was reported in the year 2021, which represents an 80% increase compared to the 2020 figure (Fletcher 2022). This justifies research attention focused on Internet fraud in order to understand what motivates the growth of Internet scams across the world (Ogunleye, Ojedokun, and Aderinto 2020;Uroko 2021), to understand the factors influencing vulnerabilities to being scammed (Hanoch and Wood 2021;Kadoya et al 2021) and reporting behaviour of victims (Kemp et al 2020), and to determine preventive measures (Whitty 2019). Similarly, existing theories have been extrapolated to explain the rise and persistence of Internet scamming (Boman and Freng 2018;Dearden and Parti 2021;Leukfeldt and Yar 2016;Louderback and Antonaccio 2021).…”
Section: Introductionmentioning
confidence: 99%